PH sensitive peptide functionalized nanoparticles for co-delivery of erlotinib and DAPT to restrict the progress of triple negative breast cancer. (1st January 2019) - Wan, Xu; Liu, Chaoqian; Lin, Yinan; Fu, Jie; Lu, Guohong; Lu, Zhengmao
Abstract: Although a variety of drug delivery strategies have been designed for enhancing the treatment of Triple negative breast cancer (TNBC), combating with TNBCs is still dramatically challenged by the selection of appropriate therapeutic targets and insufficient tumor accumulation or inner penetration of chemotherapeutics. To address these issues, the classical EGFR-inhibitor, erlotinib (EB), was selected as the model drug here and PLA-based nano-platform (NP-EB) was prepared for tumor site drug delivery. Given the significant role of Notch-EGFR interplay in raising severe resistance to EGFR inhibition of EB, gamma secretase inhibitor (GSI)-DAPT was further entrapped into the core of nanoparticles to inhibit the activation of Notch signaling (NP-EB/DART). For achieving the goal of tumor targeting drug delivery, we developed a new peptide CF and decorating it on the surface of EB/DART-dual loaded nanoparticles (CF-NP-EB/DART). Such CF peptide was designed by conjugating two separated peptide CREKA, tumor-homing peptide, and F3, cell penetrating peptide, to together via a pH-sensitive hydrazone bond. By this way, the tumor unspecific property of F3 was sealed and significantly reduced the site effects. However, after the nanoparticles reach the tumor site, the pH-sensitive linkage can be broken down by the unique acidic environment of tumor, and subsequently discovered the F3 peptide to penetrate into tumor cells.